Aplicação do método B ao projeto formal de software embarcado - Medeiros Júnior, Valério Gutemberg de (2009)
This work shows a project method proposed to design and build software components from the software functional m del up to assembly code level in a rigorous fashion. This method is based on the B method, which was developed with support and interest of British Petroleum (BP). One goal of this methodology is to contribute to solve an important problem, known as The Verifying Compiler. Besides, this work describes a formal model of Z80 microcontroller and a real system of petroleum area. To achieve this goal, the formal model of Z80 was developed and documented, as it is one key component for the verification upto the assembly level. In order to improve the mentioned methodology, it was applied on a petroleum production test system, which is presented in this work. Part of this technique is performed manually. However, almost of these activities can be automated by a specific compiler. To build such compiler, the formal modelling of microcontroller and modelling of production test system should provide relevant knowledge and experiences to the design of a new compiler. In ummary, this work should improve the viability of one of the most stringent criteria for formal verification: speeding up the verification process, reducing design time and increasing the quality and reliability of the product of the final software. All these qualities are very important for systems that involve serious risks or in need of a high confidence, which is very common in the petroleum industry